WINDS, TEMPERATURES, AND DENSITIES OVER THULE, GREENLAND AT 25 TO 65 KILOMETERS. - Kantor,Arthur J. (1969)
Preliminary estimates of mean monthly and annual wind, temperature and density patterns at Thule AFB are provided for altitudes 25 to 65 km. Maximum mean monthly zonal winds occur during the solstice months. Values are 30 mps from the east in June and nearly 60 mps from the west in December. The meridional wind flow is generally weaker and not as definitive as the zonal patterns. The warmets mean monthly temperatures approach 290K in June and early July at the stratopause, slightly above 50 km. The coldest stratopause apparently occurs in November or possibly December, but its temperature, roughly 260K, and height are not so obvious. The maximum annual range of mean monthly temperatures at altitudes 25 to 65 km approaches 55K at 40 km. At 25 km rocketsonde temperatures are 3K warmer, on the average, than temperatures derived from concurrently launched radiosondes. The maximum difference ranged from +6 to -3K. Lowest densities near the stratopause occur in winter and highest densities occur in summer. Mean monthly departures from the U.S. Standard Atmosphere, 1962, approach +40% near 60 km in summer and decrease to 40% or 45% below Standard above 50 km in February. Densities above 50 km for December and January may be 10% or 15% lower than the February values. (Author)